Clinical factors associated with circulating tumor DNA (ctDNA) in primary breast cancer - Yidong Zhou; Yaping Xu; Yuhua Gong; Yanyan Zhang; Yaping Lu; Changjun Wang; Ru Yao; Peng Li; Yanfang Guan; Jiayin Wang; Xuefeng Xia; Ling Yang; et al. (Molecular Oncology)
Noninvasive circulating tumor DNA (ctDNA) can be used to predict breast cancer recurrence and prognosis. In this study, we detected 226 and 114 somatic variants in tumor DNA from 70 primary breast cancer (PBC) patients (98.59%) and ctDNA from 48 patients (67.61%), respectively. Gene frequencies of tumor DNA and ctDNA significantly correlated (R2 = 0.9532, P < 0.0001), and tumor‐derived variants were detectable in the blood of 43 patients. ctDNA was more often detected in locally advanced/metastatic and nonluminal patients. Multivariate analysis revealed that individual N stage (P < 0.001) and hormone receptor (HR) status (P = 0.001) could independently predict the detectability of tumor‐derived mutations in blood. The maximal variant allele frequency of ctDNA was significantly higher in patients with stage IV/M1 (P = 0.0136) and stage T3/T4 (P = 0.0085) cancers. Finally, clonal variants in tumor DNA were more easily traced in ctDNA than subclonal variants (84.62% vs 48.75%). In conclusion, ctDNA fragments concordant with tumor DNA can be consistently detected in the majority of tested PBC patients, which may enable noninvasive genomic profiling of PBC, particularly for patients with advanced‐stage tumors and positive HR status.